The Boom, Bust and Restructuring of Indonesian Banks - Pangestu, Mari (IMF Working Papers; Working Paper ;, 2002)
This paper studies why currency and monetary shock hit Indonesia's economy and banking sector so severely and the measures that were taken to deal with the banking crisis, the lessons learned, and challenges faced in restructuring and strengthening the banking system. The vulnerable state of the banking sector, in combination with exchange rate and interest rate shocks, led to a systemic banking crisis. The priorities for bank restructuring are to complete the separation of nonviable from viable banks, recoup losses, implement new rules and regulations, and develop an incentive-based system for the consolidation of banks.